Which One Is Most Relevant About The Zakat Of Crab Trading According To Imam Asy-Syafi’i And Imam Ibn Hazmin - Kid, Eustass D (Fakultas Syari'ah dan Hukum UIN Sumatera Utara, 2022)
This thesis is entitled The Zakat of Crab Trading according To Imam Asy- Syafi’i and Imam Ibn Hazm (A Case Study of Tanjungbalai Asahan). Alms is one of Islamic pillars. Our worship will be accepted by Allah SWT, our wealth will be cleaned from dirty. Generally, there are three animals allowed for animal alms, such as cows, goats, and camels. Other than those animals are optional. How about crab trading as alms? This crab trading alms was proposed by UD SULTHAN enterprise located in Tanjungbalai Asahan. The owner said that paying alms was a mandatory. He does it every year. I choose this topic for my thesis by analyzing it from two different points of view from Imam Syafi’i and Imam Ibn Hazmin. The method used in this research was Library Research to see how the trading was practiced in the society and comparative method to compare two mazhab experts opinion. The data collection was done through an interview and related books as references.